Presidential Candidacy and Democratic Direction after Constitutional Court Decision 62/PUU-XXII/2024 - Cahaya Fitri; Ahmad Ahmad; Salsabila Maharani; Netty Arieyani; Franky Aryadi; Edi Suharjono (Universitas Muhammadiyah Tangerang, 2023)
This study seeks to examine the evolving landscape of presidential nominations and the trajectory of democracy following Decision No. 62/PUU-XXII/2024 of Indonesian constitutuional court, which abolished the presidential nomination threshold in Indonesia’s presidential elections. The research addresses how the removal of this threshold reshapes the nomination system, influences coalition-building patterns, and affects overall democratic quality. Employing a qualitative descriptive approach, the study relies on the analysis of judicial decisions, academic literature, and previous electoral data. The findings indicate that eliminating the nomination threshold opens greater space for alternative candidates who better reflect Indonesia’s political diversity. This reform reduces the dependence of smaller political parties on dominant parties and discourages the formation of superficial, purely pragmatic coalitions. Moreover, it weakens the structural dominance of major parties in controlling presidential nominations and creates opportunities for the emergence of a more robust opposition axis. Such developments are likely to foster a political environment that is healthier, more competitive, and more balanced. Consequently, the direction of democracy after this constitutional court ruling is expected to become more inclusive and to strengthen Indonesia’s multiparty political system.